The relationship between breast milk intake and speech in children with cerebral palsy - Kaya-Özçora, Gül Demet; Bektaş, Gonca (TÜBİTAK, 2021)
Background/aim: Cerebral palsy (CP) is a nonprogressive neurodevelopmental disorder that cause damage to the developing brain (0–3 years) for various reasons. Children with CP commonly have speech disorders due to impairment in neuromuscular control of oro-motor coordination. We focused on the relationship between breast milk intake and speech functions in children with CP. Materials and methods: The gross motor function classification system (GMFCS) was used to categorize the gross motor function. The viking speech scale (VSS) was used to classify the speech in children with cerebral palsy. Children were subdivided into two groups as term and preterm based on gestational age. The duration of exclusive breast milk intake was defined as the period when the infant received breast milk alone. We used Spearman’s correlation coefficient to evaluate the relationship between the duration of breast milk intake, GMFCS, and VSS. Results: The median level of viking speech scale was 2 in preterm-born children and 4 in term-born children. There was no correlation between age and VSS levels.We observed a statistically significant difference in terms of preterm- or term-born status among children with different VSS levels. There was a weak positive correlation between birth weight and VSS level, indicating better speech function in children with lower birth weight. There was a moderate negative correlation between the duration of exclusive breast milk intake, the total duration of breast milk intake, and the corrected age of weaning completion with VSS level. Conclusion: The duration of breast milk intake may reflect the oromotor function and predict speech performance in children with cerebral palsy. We wanted to emphasize that speech language therapy is as important as motor rehabilitation.Key words: Cerebral palsy, breast milk, speech disorders
Keywords: serebral palsi; anne sütü; konuşma bozuklukları